2015
DOI: 10.1007/s40011-015-0647-1
|View full text |Cite
|
Sign up to set email alerts
|

Eggshells of Drosophila melanogaster and D. simulans: Ultrastructure, Measurement and Analyses

Abstract: Phenotypic divergence of eggshells between D. melanogaster and D. simulans strains, was compared, using SEM, for analyzing fitness related eco-physiological traits of the eggshells in the two sibling species. The variations of eggshell traits between strains within species, between species and asymmetry in hybrids of two species have been calculated for understanding the demographic success of the two species. The present results revealed that variation of traits between strains within species was not always s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In our analysis of differentially expressed genes we found that those genes known to be involved in eggshell formation are upregulated in female Zhr 1 . This is of interest considering the significant differences in the ultrastructure of the chorion between D. simulans females and D. melanogaster males [73]. They showed that the chorion ridges in eggshells were thicker in D. simulans than in D. melanogaster.…”
Section: The 1688 Satellite Modulates Chorion Family Expression In Fmentioning
confidence: 98%
“…In our analysis of differentially expressed genes we found that those genes known to be involved in eggshell formation are upregulated in female Zhr 1 . This is of interest considering the significant differences in the ultrastructure of the chorion between D. simulans females and D. melanogaster males [73]. They showed that the chorion ridges in eggshells were thicker in D. simulans than in D. melanogaster.…”
Section: The 1688 Satellite Modulates Chorion Family Expression In Fmentioning
confidence: 98%